Synthesis and characterization of porous composite with tailored porosity fabricated using rice husk by utilizing red mud and coal mine tailing - Pandey V.; Pareta A.S.; Tiwari A.; Singh P.K.; Gupta A.; Panda S.K. (My University, 2025)
Management and use of red mud (RM) and coal mine overburden waste (MW) have drawn attention over the past decade due to their enormous scale and associated environmental problems. The harmful impact of this solid waste and its leachates has damaged the nearby ecosystem and forced industries to look for alternative solutions just rather than dumping. Despite having a lot of research, industries are still looking for a solid solution that can be implemented. Mass conversion with economic feasibility is the major obstacle faced by these wastes. The current work examines the potential use of these wastes for fabricating porous ceramic bricks by incorporating multiple quantities of their mixture with rice husk. The physical qualities of bricks have been studied in relation to variations in the MW: RM ratio, sintering temperature, and Rice husk amount. The developed porous composite possesses apparent porosity, compressive strength, and thermal conductivity in the range of 26–54%, 0.83–6.83 MPa, and 0.37–0.67 W/mK respectively. The developed porous composite with tunable pore microstructure is seen as a potential material for thermal insulation and other similar applications. © 2025 The Author(s).